Graphene Modified Cu2O Nanostructures for the Reductive Transformation of Nitrophenols. (2019) - Kapoor, Surbhi; Goel, Neetu; Singhal, Sonal
Abstract: Pure Cu2 O nanoparticles (NPs) and graphene modified Cu2 O nanostructures using graphene oxide (GO) as precursor for support were fabricated by a facile liquid phase dispersion method. The prepared samples were characterized by using XRD, FE-SEM and TEM. XRD studies confirmed the formation of cubic phased Cu2 O NPs. FE-SEM micrographs revealed the formation of spherical Cu2 O NPs. TEM micrographs demonstrated the successful incorporation of Cu2 O NPs on the two-dimensional graphene sheet. The catalytic performance of the prepared nanostructures was evaluated for the reductive transformation of nitrophenols to aminophenols. The significant enhancement in the catalytic efficacy was observed by the immobilization of Cu2 O NPs on graphene sheet. Synergistic bonding between Cu2 O NPs and graphene sheet is responsible for the augmentation in the catalytic activity of Cu2 O NPs.